Differential Effects of Alcoholic and Non-Alcoholic Beer Intake on Renin–Angiotensin System Modulation in Spontaneous Hypertensive Rats - María Dolores Mayas; Cristina Cueto-Ureña; María Jesús Ramírez-Expósito; José Manuel Martínez-Martos (Applied Sciences)
This study investigates the effects of alcoholic (AB) and non-alcoholic beer (NAB) consumption on blood pressure and the activity of enzymes regulating the renin–angiotensin system (RAS) in Wistar–Kyoto (WKY) and spontaneously hypertensive rats (SHRs), with WKY rats used as normotensive controls for SHRs. The RAS is crucial for long-term blood pressure regulation, with angiotensin II (AngII) being a potent vasoconstrictor. The aim was to explore the biochemical mechanisms by which beer might influence cardiovascular health. WKY and SHRs were divided into groups receiving tap water (TW), non-alcoholic beer (NAB), alcoholic beer (AB), TW or NAB and TW or AB for 12 weeks. Systolic blood pressure (SBP), body weight, and biochemical parameters (electrolytes, glucose, renal and liver function, lipid profile) were monitored, and the RAS enzyme activity in serum and various tissues was analyzed. Beer consumption, regardless of alcohol content, did not significantly affect SBP or body weight. However, NAB and AB altered the serum electrolyte levels in both strains. AB consumption increased liver enzyme activity. Significant changes were observed in the RAS enzyme activity across tissues, varying by strain, beer type, and tissue. Moderate beer consumption did not elevate blood pressure in WKY or SHRs. Nevertheless, beer modulated RAS-regulating enzyme activities, indicating potential impacts on cardiovascular homeostasis.